Analisis Strategi Implementasi Co-Firing Biomassa Pada Pembangkit Listrik Tenaga Uap Dalam Mendukung Net Zero Emission Menggunakan Soft System Methodology - Muhammad Rizki; Yenny Maya Dora (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the existing conditions of the operational, logistical, and environmental systems at PT XYZ, identify the key success factors, and formulate a conceptual model for a biomass co-firing implementation strategy. The research employs a qualitative method with a Soft System Methodology (SSM) approach to untangle the complex and unstructured problem situation (messy problem). Data collection was conducted through field observations and in-depth interviews with key informants from power plant management, logistics, and environmental teams. The systemic analysis progressed through the stages of Rich Picture, CATWOE analysis, Root Definition, and Conceptual Model development. The results indicate that PT XYZ is not yet fully prepared to implement biomass co-firing directly due to technical boiler assessment requirements, the absence of a structured biomass supply chain, and regulatory uncertainties. Through the SSM approach, a conceptual model was successfully designed as a strategic recommendation to enhance supply chain governance, modify operational infrastructure, and ensure regulatory compliance.